(In)visibilidades das juventudes pós-modernas: trilhas estéticas na cibercultura - Zacariotti, Marluce (Pontíficia Universidade Católica de Goiás, 2017)
This text addresses the (in) visibility of youths (tribes) in postmodernity, with the assumption that in the virtual spaces of confluence between technology and art they can gain visibility. The approach is anchored in theory, especially in the French thinker Michel Maffesoli, whose method the comprehensive sociology. The theoretical framework articulated the maffesoliano thought to youths as a category or metaphor way of being youthful and technological implications in the process of interaction, mediation and empowerment of youth aesthetic expressions. We use Maffesoli notions as categories to understand the new forms of tribes sociality through their various art forms in cyberspace. Flash Mobs descriptions and analyzes demonstrations posted on YouTube videos and groups that maintain website / Facebook pages for dissemination of artistic and cultural meetings mediated by cyberspace allowed realize that not all tribes operate through the same dynamic, which it led us to develop the idea of intensity of youth practices both in terms of the forms of ownership, such as how to relate to what was appropriate. The aesthetic-emotional bias leads to identify the mode of being youthful with a Dionysian spirit. As Aphrodite's metaphor (sensuality referred not only to sexuality, but freedom is sought in living without rules, a return to nature) that, for us, also round the being-together of the tribes. Therefore we find in the artistic frames a visibility of youths plenty the dialogue on physical and virtual interface and occupy public spaces in the city.